A comparative study of polypropylene/(chloroprene rubber) and (recycled polypropylene)/(chloroprene rubber) blends. Issue 2 (1st July 2014) - Salmah, H.; Azra, B. N.; Yusrina, M. D.; Ismail, H.
Abstract : The blends of virgin polypropylene (PP) and recycled polypropylene (RPP) with chloroprene rubber (CR) have been prepared. The effect of different blend ratios on tensile properties, swelling behavior, morphology, and crystallinity of both blends of virgin and RPP was investigated. The tensile strength and Young's modulus of both blends decreased with increasing CR in blend ratios but the elongation at break was increased. It was found that the tensile properties of PP/CR blends were better than the RPP/CR blends. The PP/CR blends showed the lower value of swelling index. The scanning electron micrograph of the tensile fractured surface of PP/CR blends indicates that a higher energy is needed to cause failure compared with RPP/CR blends. The differential scanning calorimery results indicated that the degree of crystallinity of PP/CR blends also was found to be higher than RPP/CR blends. J. VINYL ADDIT. TECHNOL., 21:122–127, 2015. © 2014 Society of Plastics Engineers